Peran Usaha Kuliner Lokal dalam Peningkatan Kesejahteraan Karyawan: Studi Kasus Rumah Makan Uda Nasrul - Ruslan Ruslan; M. Arif Musthofa; Hasna Dewi; Erwina Kartika Devi; Daud Daud (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the role of Rumah Makan Uda Nasrul in improving the welfare of its employees in Kelurahan Mendahara Ilir, Kecamatan Mendahara, Kabupaten Tanjung Jabung Timur. This study explores how a single small-scale food business can significantly contribute to the economic and social well-being of its workers, particularly in rural areas with limited employment opportunities. The focus is on income stability, working environment, and the indirect social benefits gained by the employees. Materials and methods. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. Primary data were gathered from in-depth interviews with employees and the business owner, while secondary data included relevant documents and local employment statistics. The analysis used interactive techniques involving data reduction, data display, and conclusion drawing. The selection of Rumah Makan Uda Nasrul as the research site was based on its consistent employment of local labor and its established reputation within the community. Results. Click here and insert your text. Click here and insert your text. Click here and insert your text. The findings indicate that Rumah Makan Uda Nasrul provides a reliable monthly income ranging from Rp1,200,000 to Rp1,800,000 per employee, along with daily incentives and meal allowances. The work atmosphere is characterized by a strong sense of kinship, flexibility, and mutual respect. While formal social security programs like BPJS are not yet available, employees report increased financial independence, skill development, and improved quality of life due to stable employment. Conclusions. Rumah Makan Uda Nasrul plays a meaningful role in elevating employee welfare through stable income, a supportive work environment, and opportunities for informal learning. This case demonstrates how small local enterprises can serve as effective agents of community-based economic development.